Cu2ZnSnS4 thin film solar cells grown by fast thermal evaporation and thermal treatment. (1st January 2017) - Garcia-Llamas, E.; Merino, J.M.; Gunder, R.; Neldner, K.; Greiner, D.; Steigert, A.; Giraldo, S.; Izquierdo-Roca, V.; Saucedo, E.; León, M.; Schorr, S.; Caballero, R.
Graphical abstract: Highlights: Cu2 ZnSnS4 thin films deposited by thermal evaporation in 12 min plus annealing. The presence of SnS next to the Mo layer limited the device efficiency about 3%. An increased Voc was achieved by using a Zn(O, S) alternative buffer layer. Abstract: Cu2 ZnSnS4 thin films have been produced via rapid thermal evaporation of off-stoichiometric kesterite powder followed by annealing in an Ar atmosphere. Different heating rates were applied during the thermal treatments. The chemical composition and structural properties of the deposited layers as well as the distribution of the elements through the kesterite thin film have been investigated. The initial growth of a SnS secondary phase during evaporation led to the formation of this secondary phase next to the Mo back contact. Solar cell power conversion efficiencies were limited to values about 3% due to this secondary phase. Furthermore, an increased open circuit voltage was demonstrated by using a Zn(O, S) buffer layer.